DESIGN AND CONSTRUCTION OF THE ALTERNATIVE CONTROL SYSTEM FOR NEUTRON DIFFRACTOMETERS AND SPECTROMETERS AT PTBIN, BATAN - Eddy Santoso (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2008)
ABSTRACT DESIGN AND CONSTRUCTION OF THE ALTERNATIVE CONTROL SYSTEM FOR NEUTRON DIFFRACTOMETERS AND SPECTROMETERS AT PTBIN-BATAN. The alternative control systems based on programmable peripheral interface (PPI) IC 8255 and programmable interval timer (PIT) IC 8253 have been developed to control the neutron diffractometer and spectrometer instruments at Center of Technology for Nuclear Industrial Materials (PTBIN)-BATAN which had defective control systems. This alternative control system has been installed at Four Circle Diffractometer/Texture Diffractometer (FCD/TD),  High Resolution Powder Diffractometer (HRPD) and Triple Axis Spectrometer (TAS). The control system components were assembled as a plug-in printed circuit board (PCB) at the ISA slot of a personal computer. IC PPI 8255 was programmed to control the mechanical movements of the instruments and IC PIT 8253 was programmed as a main counter and used as programmable monitor counter. The testing either with or without neutrons has shown that this alternative control system can be used to control the neutron diffractometers and spectrometers also the result shows that this system is in a good performance. Key words: Alternative control system, neutron diffractometer and spectrometer, interface, monitor counter and main counter.   ABSTRAK RANCANG BANGUN SISTEM KENDALI ALTERNATIF UNTUK PERALATAN DIFRAKTOMETER DAN SPEKTROMETER NEUTRON DI PTBIN, BATAN. Telah dikembangkan sistem kontrol alternatif yang berbasis pada programmable peripheral interface (PPI) IC 8255 dan programmable interval timer (PIT) IC 8253 untuk mengendalikan peralatan difraktometer dan spektrometer neutron di Pusat Teknologi Bahan Industri Nuklir (PTBIN) - BATAN yang sistem kendalinya sudah tidak berfungsi. Sistem kendali alternatif telah diterapkan pada difraktometer empat lingkaran/difraktometer tekstur (FCD/TD), difraktometer serbuk resolusi tinggi (HRPD) dan spektrometer tiga sumbu (TAS). Komponen-komponen sistem kendali dirakit pada papan rangkaian cetak (PCB) yang dipasang pada slot ISA komputer pribadi. IC PPI 8255 diprogram untuk mengendalikan gerakan mekanik peralatan dan IC PIT 8253 diprogram sebagai pencacah utama dan pencacah monitor. Hasil pengujian baik dengan neutron maupun tanpa neutron menunjukkan bahwa sistem kendali alternatif dapat digunakan dan berfungsi dengan baik untuk mengendalikan difraktometer dan spektrometer neutron. Kata Kunci: Sistem kendali Alternatif, difraktometer dan spektrometer neutron, antarmuka, pencacah monitor dan pencacah utama.